Cool pavement - Tan, Xin Wei (2019)
Cool pavement refers to pavements paved with a range of emerging materials. These materials enable lesser heat absorption on the pavement and help to address the problem of urban heat islands, which is often a result from increased temperatures in paved surfaces in a city. One of the possible ways is to improve solar reflectivity of pavements, whereby ordinary portland cement is substituted with white cement to create a whiter surface. Alternatively, the addition of titanium oxide into conventional concrete mix can achieve similar effects. Titanium oxide additives also helps in mitigating the international pollution problem due to its self-cleansing properties. When infused in concrete, it can break down and render harmless the air pollutants. However, considerations such as cost, physical and thermal properties of the element’s dosage need to be considered thoroughly to achieve optimum results. To further enhance the durability of pavements, conventional concrete was replaced wholly with engineered cementitious composites (ECC). This reduces the effect of brittle fracture failure due to repeated loadings. In this study, the above alterations were applied to create the composite (cool pavement) specimens and a temperature prediction model was created. Validation of model was done by comparing the experimental and modelled temperatures. Based on the validation of different composites coupled with parametric study, the suitability of the prediction model for this pavement type was concluded. Recommendations to carry on further research of the selected materials and model were also addressed.